Participant and Musical Diversity in Music Psychology Research - Kelly Jakubowski; Nashra Ahmad; James Armitage; Logan Barrett; Aliya Edwards; Elizabeth Galbo; Juan S. Gómez-Cañón; Thomas A. Graves; Akvilė Jadzgevičiūtė; Connor Kirts; Imre Lahdelma; Thomas M. Lennie; et al. (Music & Science)
Research on music psychology has increased exponentially over the past half century, providing insights on a wide range of topics underpinning the perception, cognition, and production of music. This wealth of research means we are now in a place to develop specific, testable theories on the psychology of music, with the potential to impact our wider understanding of human biology, culture, and communication. However, the development of more widely applicable and inclusive theories of human responses to music requires these theories to be informed by data that is representative of the global human population and its diverse range of music-making practices. The goal of the present paper is to survey the current state of the field of music psychology in terms of the participant samples and musical samples used. We reviewed and coded relevant details from all articles published in Music Perception , Musicae Scientiae , and Psychology of Music between 2010 to 2022. We found that music psychologists show a substantial tendency to collect data from young adults and university students in Western countries in response to Western music, replicating trends seen across psychology research as a whole. Even data collected in non-Western countries tends to come from a similar demographic to studies of Western participants (e.g., university students, young adults). Some positive trends toward increasing participant diversity have been evidenced over the past decade, although there is still much work to be done, and certain subtopics in the field appear to be more prone to these sampling biases than others. We discuss recent methodological developments in the field that promote further diversification of our research and highlight subsequent changes that will be needed at group or institutional levels.